Antibacterial activity assay from Porphyridium cruentum microalgae - KUSMIYATI KUSMIYATI; NI WAYAN SRI AGUSTINI (Biodiversitas Journal of Biological Diversity, 2007)
The objective of this research was to know the antibacterial activity from the Porphyridium cruentum. P. cruentum is the Rhodophyceae algae. The extraction of microalgae biomass used dichloromethane solution and resulted three types extracts. Antibacterial activity of the extracts using the clear zone method to Escherichia coli, Bacillus subtilis and Staphylococcus aureus bacteria. Identification of antibacterial substance of the extracts were using Gas Chromatograph Mass Spectrophotometer (GCMS). The results showed that C type extract have antibacterial activity to all of indicator bacteria, neither do A type extract. Whereas the B type extract inhibited to B. subtilis and S. aureus growth. Analysis of the antibacterial compound by GC-MS was fatty acid. The major component of antibacterial from the P. cruentum was metil hexadecanoate acid (palmitic acid), the percent area was 41,15 % of B type extract and 60,36 % of C type extract.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words : Porphyridium cruentum, dichlorometane extract, antibacterial activity, GCMS